Isolated Para-Aortic Lymph Nodes Recurrence in Carcinoma Cervix - Ghimire, S; Hamid, S; Rashid, A (Journal of Nepal Health Research Council, 2010)
Background: To evaluate the presentation of isolated para-aortic lymph node recurrence after definitive treatment, and to analyze the effect of salvage treatment on the survival rate. Methods: A retrospective study was done for patients with invasive carcinoma of the uterine cervix treated with various modalities of treatment at Shaukat Khanum Memorial Cancer Hospital Research Center Lahore Pakistan from December, 1999 to August 2004. Results: The incidence of radiographically detected para aortic lymph node recurrence was 3.7% by FIGO stage at original diagnosis was 3 (50 %) in stage IIIB, 2 (33.3%) in post hysterectomy status and 1 (16.7%) in stage IB cervical carcinoma. Total 4 (66.7%) patients with para-aortic lymph nodes recurrences were identified with in the first 12 months after the initial treatment and 2(33.3%) had their recurrence after 12 month. Leg swelling, low back pain and hydronephrosis were observed when inquired for the presentation in those patients with recurrence in paraarotic lymph nodes. Hydronephrosis was the commonest finding (50%) either alone or in association with other symptoms. And 3 (50%) of the patient were died within two year of the diagnosis of recurrence.Three patients are still on follow up, one with progressive disease in liver and one with chronic renal failure, and one asymptomatic. Patient who received radiation alone had overall survival of 3.16 months after the recurrence compared with >12 months overall survival for those treated with chemotherapy. Conclusions: Symptoms like leg swelling, low back pain and hydronephrosis helps a lot to detect the early paraaortic recurrence, hydronephrosis being commonest. Although the number of patients with para-aortic recurrence were very small and the follow up time was too short to make any recommendations for salvage treatment or survival advantages, as a definitive treatment for isolated para aortic lymph nodes we can offer both radiotherapy or chemotherapy. Key words: cervix; carcinoma; lymph nodes; para-aortic; recurrence. DOI: 10.3126/jnhrc.v7i2.3016 Journal of Nepal Health Research Council Vol.7(2) Apr 2009 103-107